Empowering Indonesian women through UN Women: A Marxist Feminist analysis of policies and their impact - Shofi Thowil Umur; M. Nur Rofiq Addiansyah; Ammar Salem Khan (Institute for Research and Community Service, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, East Java, Indonesia., 2025)
Indonesia continues to face structural gender discrimination that limits women’s empowerment, while United Nations (UN) Women programs are constrained by patriarchal norms, unequal resource distribution, and limited access in remote areas. The aim of this study is to analyze the role of UN Women Indonesia in advancing gender equality through advocacy, national campaigns, economic empowerment, and technological innovation, as well as to evaluate the alignment of its programs with Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW) and the global gender agenda. A descriptive qualitative approach was employed, focusing on policy advocacy, public education, and multi-actor collaboration, while data validity was strengthened through triangulation of social media, official websites, and academic literature. The findings show that: (1) UN Women Indonesia implements three pillars and three strategic functions, although field-level challenges remain; (2) multi-level programs reach 88 cities across 18 provinces, but local sustainability and impact measurement remain weak; and (3) women’s political participation is still at 22%, and Indonesia’s position in Association of Southeast Asian Nations (ASEAN) remains suboptimal, indicating the need for stronger and sustained cross-sector collaboration. This study concludes that UN Women Indonesia plays a strategic role in reaching 88 cities; however, substantive gender equality has not been achieved due to patriarchy, class inequality, and unequal access to services. The study contributes by integrating Marxist feminist perspectives and evaluating technological innovation as a form of structural transformation, while emphasizing resource redistribution and men’s engagement as essential for substantive gender equality.